Volume 4: Heat Transfer; Electric Power; Industrial and Cogeneration 1994
DOI: 10.1115/94-gt-182
|View full text |Cite
|
Sign up to set email alerts
|

Film Cooling Effectiveness and Heat Transfer Coefficients for Slot Injection at High Blowing Ratios

Abstract: In continuation of earlier studies comparing heat transfer results for flow over a backward facing step and a jet in crossflow, a comprehensive data base for slot film cooling is presented. Specifically, heat transfer measurements adjacent to the injection slot for high blowing ratios were of interest. The heat transfer distributions for these conditions are of increasing significance in modern combustor liners. The new data base includes velocity and temperature profile measurements, adiabatic wall temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Taslim et al (1992) investigated the effect of parameters like density ratio, lip thickness to ejection slot height ratio (t/s), slot width to height ratio (w/s) and injection angle on the adiabatic effectiveness distribution downstream of a simplified trailing edge model in a non accelerating flow. Bittlinger et al (1994) studied the injection through a slot at high blowing conditions on a similar model varying both the lip thickness and the slot height. Martini et al (2005a) measured g downstream of a cutback trailing edge model (t/s = 1.0), for three internal cooling configurations, at low and constant mainstream velocity.…”
Section: Cutback Trailing Edge Studiesmentioning
confidence: 99%
“…Taslim et al (1992) investigated the effect of parameters like density ratio, lip thickness to ejection slot height ratio (t/s), slot width to height ratio (w/s) and injection angle on the adiabatic effectiveness distribution downstream of a simplified trailing edge model in a non accelerating flow. Bittlinger et al (1994) studied the injection through a slot at high blowing conditions on a similar model varying both the lip thickness and the slot height. Martini et al (2005a) measured g downstream of a cutback trailing edge model (t/s = 1.0), for three internal cooling configurations, at low and constant mainstream velocity.…”
Section: Cutback Trailing Edge Studiesmentioning
confidence: 99%
“…When heat transfer coefficients are required, the surface temperature and the heat flux must be measured. Thermocouples or resistance thermometers positioned at specific positions along the surface are commonly used for temperature measurements [5,6]. However, the ready accessibility of easy-to-use thermography caused a paradigm shift for surface temperature measurements.…”
Section: State Of the Artmentioning
confidence: 99%
“…For heat flux measurements different steady and transient techniques exist. Steady heat flux measurements either calculate the heat flux through a material of known thermal conductivity by measuring the temperatures on both sides [6,11,12], or record the local heat flux with the help of heat flux sensors, e.g., thin-film heaters [9,10,13]. Carlomagno [18] reviewed different types of heat flux sensors and concluded that thin-film heaters are precise and effective devices.…”
Section: State Of the Artmentioning
confidence: 99%
“…One of the recent studies in tangential slot jet film cooling was done by Bittlinger, Schulz, and Wittig (1994). With a density ratio of unity, they conducted heat transfer coefficient experiments over a range of blowing ratios (0.55<M<3.2).…”
Section: Introductionmentioning
confidence: 99%